Eksplorasi Pemanfaatan Film Berbahasa Inggris Terhadap Pembelajaran Vocabulary Dan Listening Mahasiswa Pendidikan Bahasa Inggris - Arina Mana Sikana; Alison Theend Artha; Wiwin Luqna Hunaida (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2026)
This study aims to determine the perceptions of English Language Education students regarding the effectiveness of English-language films as a learning medium for enriching vocabulary and improving listening skills. This study employed a quantitative descriptive approach among English Education students in Class A at UIN Sunan Ampel Surabaya, with a total of 33 respondents. Data were collected via a questionnaire consisting of 10 questions, each with five response options: strongly agree, agree, neutral, disagree, and strongly disagree. The data obtained were then analyzed descriptively using percentage calculations based on the respondents’ answers to each question. The results showed that 93.9% of students stated that English-language films help improve vocabulary, 97% stated that films help improve listening skills and enhance their understanding of various accents and intonations, and 84.9% of students agreed that English-language films are effective as a learning medium. Therefore, based on the students’ perceptions, it can be concluded that the use of English-language films is effective as a learning medium for improving students’ listening skills and enriching their vocabulary.